ACCOUNTING AND INTERNAL AUDIT IN HIGHER EDUCATIONAL INSTITUTIONS - Ermatova Sakhodatkhon , Ismailovna (THE INNOVATION ECONOMY, 2025)
This article examines the overall state of liabilities accounting and internal audit processes in Uzbekistan’s higher education institutions (HEIs). The study explores the impact of liabilities accounting on financial reporting quality and the role of internal audit in oversight and optimization. A mixed-methods approach was employed, combining qualitative analysis (of regulatory documents) and quantitative analysis (of financial metrics from 5 HEIs over 2020–2024). Findings indicate that the accuracy of liabilities accounting hinges on effective internal audit systems, yet infrastructure limitations, insufficient staff qualifications, and regulatory inconsistencies persist as challenges. The article provides practical recommendations for enhancing financial management in HEIs.